A study of factors leading to osteo-penia in the community: BMD camp based approach - Mishra, Santosh Kumar; Trivedi, Anshuli; Trivedi, Anubhooti (International Journal Of Community Medicine And Public Health, 2017)
Background: Osteoporosis is an important public health problem in times of increasing life expectancy. A large number of cases are undiagnosed resulting in bone fragility & fractures. Bone mineral density reduces physiological in both sexes, but it is more rampant in women in hypoandrogenic states, i.e. post menopause. Methods: A community based bone mineral density estimation camp was organized in a private health facility catering to the urban community in Jabalpur district of M.P during February 2015. In the camp bone mass density of attendees was assessed using DEXA technique & WHO criteria based on T score were used in the study to assess the bone mineral density. Information about social-demographic condition along with brief medical & surgical history was elicited. The results were presented in terms of percentage & proportions. The tests of significance were used for establishing associations between variables. Results: In total 298 persons attended the camp. There is a statistically significant association between prevalence of decreased BMD with age (p<0.001). In total, 55.74 % female attendees had T-score < -1.0. Hysterectomiesed women had statistically significant lower mineral densities. There is a significant association between regular alcohol intake & decreased BMD as all the Osteoporotic men in the study had BMD < -2.5. Conclusion: A camp based approach helps in identifying subclinical cases of Osteopenia in the community.